Plight itinerary: Aeromobility and the spatio-cultural politics of precarious language in Filipino labour migration - Quizon, Juan Miguel Leandro (Journal of Modern Languages, 2025)
Airport spaces are typically characterized by surveillance, security, screening, and social sorting. Transitional and liminal in nature, these mega-infrastructures are witnesses to millions of passengers (travellers, labour migrants, and refugees) as they traverse these halls and gateways toward leisure, livelihood, and even safety. While passenger and aircraft statistics are fundamental to airport studies, scholars are focusing on a vital aspect that makes airports efficient transport infrastructures of the modern world: mobility. In this paper, I investigate aeromobility, a multi-layered term pertaining to “mobility-systems, norms, embodied practices, and lifestyle discourses” that intersect with socio-cultural implications occurring within aviation spaces and air transportation in general (Zuskáčová, 2020). Particularly, I examine digital contents created and published by Filipino labour migrants focusing on their lived experiences and narratives inside international airports. Through the use of precautionary language, content creators utilize a specific language of precarity that assures other Filipino migrant workers a safer and more secure experience while traversing airport spaces. Ultimately, I argue that this deployment of precarious language eventually fosters solidarity and movement towards reclaiming their identities as part of the global workforce.